The Influence of Maturation on Sprint Performance in Boys over a 21-Month Period. Issue 12 (December 2016) - MEYERS, ROBERT W.; OLIVER, JON L.; HUGHES, MICHAEL G.; LLOYD, RHODRI S.; CRONIN, JOHN B.
ABSTRACT: Purpose: This study examined how the characteristics of maximal overground sprint performance are affected by the period of peak height velocity (PHV) in boys. Methods: One hundred eighty-nine school-age boys completed two assessments of maximal sprint performance, separated by a 21-month period. Kinematic characteristics of sprint performance were collected during a 30-m sprint using a floor-level optical measurement system, with modeled force and stiffness characteristics also calculated. Participants were grouped according to maturation using a noninvasive predictive equation. Individuals whose maturity offset was <−0.5 yr in both assessments were classed as "pre-PHV" ( n = 67), whereas those whose maturity offset developed from <−0.5 to >0.5 yr in test two were classed as "pre-to-post PHV" ( n = 39). Participants with a maturity offset between >−0.5 and <0.5 yr at test 2 were removed from analysis ( n = 67) to ensure that the entire pre-to-post-PHV group had experienced the PHV spurt. Results: The pre-to-post-PHV group experienced significantly greater increases in speed (10.4% vs 5.6%) and relative vertical stiffness (12.1% vs 5.6%) compared with the pre-PHV group. Step frequency declined (−2.4%) and contact time increased (2.3%) in the pre-PHV group, whereas step frequency increased (2.7%) and contact time decreased (−3.6%) in the pre-PHV to post-PHV group. Changes in relative measures of vertical stiffness, maximal force, and leg stiffness accounted for 79% and 83% of the changes in speed between assessments for pre-PHV and pre-to-post-PHV groups, respectively. Conclusions: As boys experience PHV, there are greater increases in maximal sprint speed compared with those who remain pre-PHV. Furthermore, measures of relative stiffness and relative maximal force appear to exert an important influence on the development of maximal sprint speed in boys, regardless of maturity.